2016
DOI: 10.1007/s11085-016-9669-1
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Deposit-Induced Accelerated Attack of MCrAlY Systems at 1100 °C

Abstract: The reaction of cast NiCoCrAlY alloys with oxide-sulfate deposits in CO 2-H 2 O-O 2 was studied at 1100 • C. The minimum Al concentration needed to form an external Al 2 O 3 scale was increased compared with depositfree exposures, as Al 2 O 3-forming compositions transitioned to internal Al 2 O 3 and external Cr 2 O 3 growth in the presence of certain deposits. Model deposits were used to investigate the role of each constituent in the complex reaction morphology observed with an industrial fly-ash. Two main m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…Alloy composition effects were studied by varying the β phase fraction and the Cr content. In general, β-rich alloys were immune to the Na silicate (NS), and formed external Al 2 O 3 scales, while some γ-rich alloys suffered internal oxidation [2]. The situation of exclusive external scaling will be considered to evaluate the validity of the oxidation-dissolution analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alloy composition effects were studied by varying the β phase fraction and the Cr content. In general, β-rich alloys were immune to the Na silicate (NS), and formed external Al 2 O 3 scales, while some γ-rich alloys suffered internal oxidation [2]. The situation of exclusive external scaling will be considered to evaluate the validity of the oxidation-dissolution analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Any process consuming the scale would result in an increased oxidation rate. In recent studies [1][2][3], we showed that Al 2 O 3 -scale forming NiCoCrAlY compositions in air were susceptible to accelerated corrosion in the presence of oxide-sulfate deposits. Two modes of attack were identified, which involved Al 2 O 3 reaction with CaO to form Ca aluminates, and Al 2 O 3 dissolution in molten Na silicate.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As beneficial as REs may be when added in the right proportion, overdoping can have detrimental consequences on oxidation resistance. Not only does overdoping increase overall scaling rates, but more critically, it produces oversized pegs which may favor scale failure during thermal cycling [15,16], or act as initiation sites for accelerated corrosion under sulfate [17] or oxide-sulfate deposits [18]. Controlling RE additions, together with impurities such as S or C, is therefore a critical aspect of material design and manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium chromate formation was a rapid, transient process, and the transition to a steady-state of slower Al 2 O 3 growth was favored by increasing the alloy β fraction. The thermallygrowing Al 2 O 3 reacted with the deposit to form calcium aluminates in a solid-state diffusion process, which led to an increased oxidation rate which has recently been attributed to hot corrosion [45,46].…”
Section: Implications: Cmas Degradation Mechanismmentioning
confidence: 99%